Representações sociais e organização do poder político: a engenharia social do federalismo no Brasil Império - Cunha, Augusto Paulo Guimarães (2001)
This research has verified by which way the representations of the social world can influence choices, referring to political systems models, specially on the power division and organization among central and undernational governments. We studied the history of these choices during the period between 1822-1889, when the question of federalism was closely articulated with problem solutions that were decisive to the construction of the Brazilian State and Nation. Theoretical reference was the approach of social relations developed by French sociologists, historians and psychologists which privilege the articulation between the agents and the social structures. The study has allowed the conclusion that the practices of federalism, during the analyzed period just make sense if they are examined from a network of representations shared by the politic leading circles in reference to de State, the Society and the relations that must exist between them.